Opening van de 5e kruidenierswinkel aan de Ferdinand Bolstraat 53. Uit: De Notenkraker 29-09-1907 - Pezaro, L.,
Opening van de 5e kruidenierswinkel aan de Ferdinand Bolstraat 53. Uit: De Notenkraker 29-09-1907.